2022
DOI: 10.1097/iae.0000000000003420
|View full text |Cite
|
Sign up to set email alerts
|

Role of Optical Coherence Tomography Angiography in Detecting and Monitoring Inflammatory Choroidal Neovascularization

Abstract: Purpose: To investigate the utility of optical coherence tomography angiography (OCTA) for the detection of inflammatory choroidal neovascularization (iCNV) and monitoring their response to treatment.Methods: A retrospective review of patients with a diagnosis of uveitis and associated iCNV with active exudation was performed. Active iCNV was determined by spectral domain OCT and/or fluorescein angiogram. Spectral domain OCTA outer retina to choriocapillaris slabs was evaluated for the presence of iCNV. Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…En face OCT, which is widely used in retinal and choroidal diseases (Gallo et al, 2022;Kongwattananon et al, 2022), has been used to visualize vasculatures. Recent advancements in hardware and software have facilitated the incorporation of posterior segment OCT technologies into anterior segment OCT systems, enabling imaging that is free from motion artifacts and providing enhanced resolution and depth penetration.…”
Section: Discussionmentioning
confidence: 99%
“…En face OCT, which is widely used in retinal and choroidal diseases (Gallo et al, 2022;Kongwattananon et al, 2022), has been used to visualize vasculatures. Recent advancements in hardware and software have facilitated the incorporation of posterior segment OCT technologies into anterior segment OCT systems, enabling imaging that is free from motion artifacts and providing enhanced resolution and depth penetration.…”
Section: Discussionmentioning
confidence: 99%
“…OCT-A was shown to be useful and a help in the detection of choroidal neovascularization (CNV) such as in MFC/PIC and other choriocapillaritis entities as well as its followup during anti-VEGF treatment but none of the articles recommended it as an exclusive use. [29][30][31][32][33][34] One report indicated that OCT-A could possibly better identify new vessels obscured by retinal haemorrhage [35]. OCT-A has been reported to be useful to distinguish CNV from active uveitic lesions [36].…”
Section: Optical Coherence Tomography Angiography (Oct-a)mentioning
confidence: 99%
“…Spectral-domain (SD) OCTA and swept-source (SS) OCTA have been found useful to study inflammatory chorioretinal diseases [ 3 , 4 , 5 , 6 , 7 , 8 ]. For example, inflammatory chorio retinal neovascularization (iCNV) can be imaged with OCTA, as it yields high-resolution images of abnormal vasculature [ 9 ].…”
Section: Introductionmentioning
confidence: 99%